2017
DOI: 10.4067/s0034-98872017001201579
|View full text |Cite
|
Sign up to set email alerts
|

Alteraciones del neurodesarrollo en pacientes con hipotiroidismo congénito: Recomendaciones para el seguimiento

Abstract: Congenital hypothyroidism (CH) is the most common cause of preventable cognitive disability worldwide. Generally, it is produced by an alteration in the embryogenesis of the thyroid gland or by an alteration in the synthesis of thyroid hormones, which determine that affected patients have low or absent thyroid hormone concentrations. The importance of this fact is that brain development during the first three years of life is highly dependent on thyroid hormones. Prior to the implementation of national neonata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 18 publications
1
18
0
5
Order By: Relevance
“…Research has shown differences in the language skills of children with CH (9,(13)(14)(15)18,25) , although there are controversial results regarding the language of this population (16,17) . Bulus and Tiftik (17) found no statistically significant differences in language in a comparison between individuals with and without CH.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Research has shown differences in the language skills of children with CH (9,(13)(14)(15)18,25) , although there are controversial results regarding the language of this population (16,17) . Bulus and Tiftik (17) found no statistically significant differences in language in a comparison between individuals with and without CH.…”
Section: Discussionmentioning
confidence: 99%
“…The literature points to this issue, stating that early diagnosis and treatment of CH are extremely important to prevent intellectual disability (7)(8)(9)15,20) . However, it also states that children with CH may present lower cognitive test results compared with their peers (7,12,18) . A study showed that children with CH, despite not presenting intellectual disabilities, had lower scores compared with siblings without metabolic disorders (12) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations